A communicative approach to conflict, forgiveness, and reconciliation reimagining our relationships - Kelley, Douglas L.; Waldron, Vincent R.; Kloeber, Dayna N. (New York Routledge, 2019)
"A Communicative Approach to Conflict, Forgiveness, and Reconciliation: Reimagining Our Relationships synthesizes communication and psychology scholarship that focuses on rebuilding ourselves and our relationships when things go "wrong". It provides fresh insights into the burgeoning body of forgiveness research, with an emphasis on community applications and reconciliation. Written by award winning scholars in forgiveness communication, the book makes forgiveness and reconciliation research accessible to students in courses focused on personal relationships, conflict, and family studies"--Provided by publisher.
Reimagining our relationships : when things go "wrong" -- (Re)imagining healthy relationships -- What went wrong? Catalysts for relational change -- Emotional response : motivation for relational change -- Sense making : understanding relational change -- Forgiveness : reimagining our response to personal pain -- Reconciliation : (re)imagining a new future -- Reimagined relationships, community applications.
Includes bibliographical references and index.
Keywords: Interpersonal communication; Interpersonal conflict; Forgiveness; Reconciliation